INTERPOLATION AND SMOOTHING L-SPLINES, FAST ALGORITHMS - Kounchev, Ognyan; Tsachev, Tsvetomir (Comptes rendus de l'Academie bulgare des Sciences, 2017)
We study fast algorithms for interpolation and smoothing by means of the one-dimensional L-splines, to which the computation of the polysplines is reduced. For these L-splines, we provide a generalization of the fast Reinsch algorithm which is famous from the computation of smoothing cubic splines, cf. [2,12]. We emphasize on the explicit expressions for all entries involved which permits a direct numerical implementation.Key words: interpolation, nonparametric regression, splines, L-splines 2010 Mathematics Subject Classification: 65D07, 65D10, 45L05